Direct observation of charge separation in an organic light harvesting system by femtosecond time-resolved XPS - Friedrich Roth (Nature Portfolio, 2021)
Understanding ultrafast dynamics of photon-to-charge conversion is paramount for optimising light-harvesting systems. Here, the authors use femtosecond time-resolved X-ray photoemission spectroscopy to reveal specific charge separation sites and monitor free charge formation in a model donor-acceptor system.